Broad Strokes and Bright Lines: A Reconsideration of Shari’a Based Reservations - Monforte, Tanya (Columbia Journal of Gender and Law, 2017)
One of the most politically charged as well as legally technical problems occupying the field of international women’s rights revolves around the reservations made to the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). An opposition among states became heated as several Muslim-majority states entered reservations to CEDAW invoking norms of Islamic Law, or Shari’a (sometimes referred to as either “Islamic reservations” or “Shari’a based reservations”). Several European states in turn lodged formal objections to these reservations. The row between European states and Muslim-majority states over the reservations has formed the basis for the technicalization of conflicting views on women’s rights, in the depoliticizing sense of turning a political conflict into a seemingly technical legal one.